2012
DOI: 10.1111/j.1750-3841.2012.02865.x
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit (Citrus paradisi Macfad) Phytochemicals Composition Is Modulated by Household Processing Techniques

Abstract: Grapefruits (Citrus paradisi Macfad) contain several phytochemicals known to have health maintaining properties. Due to the consumer's interest in obtaining high levels of these phytochemicals, it is important to understand the changes in their levels by common household processing techniques. Therefore, mature Texas "Rio Red" grapefruits were processed by some of the common household processing practices such as blending, juicing, and hand squeezing techniques and analyzed for their phytochemical content by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…This is consistent with previously reported data. Uckoo et al (12) reported that the concentration of ascorbic was significantly higher in grapefruit juice that had been processed by juicing, while the concentration of citric acid was significantly higher in grapefruit juice that had been processed by blending. As shown in Table 1, the most abundant organic acid present in the apple juices was malic acid (3,744.5∼4,091.6 μg/mL), and the least abundant organic acid present in the apple juices was ascorbic acid (38.2∼112.2 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with previously reported data. Uckoo et al (12) reported that the concentration of ascorbic was significantly higher in grapefruit juice that had been processed by juicing, while the concentration of citric acid was significantly higher in grapefruit juice that had been processed by blending. As shown in Table 1, the most abundant organic acid present in the apple juices was malic acid (3,744.5∼4,091.6 μg/mL), and the least abundant organic acid present in the apple juices was ascorbic acid (38.2∼112.2 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the effect of different household processing techniques on fruit phytochemical levels would be of interest to consumers seeking to obtain higher levels of these compounds (10,11). Previous studies report that juice extraction methods significantly influence chemical components levels and antioxidant activity of fruit (11,12). Rajasekar et al (11) suggest that blending is more efficient than mechanical press juice extraction at preserving the overall physico-chemical characteristics of pomegranate juice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each 20 μl fraction was injected into a HPLC column (Luna C18; 15 cm x3.0 mm; Phenomenex, USA) by using a modified method of Uckoo et al, 2012(Uckoo et al, 2012. Gradient elution was conducted at a flow rate of 1.5 ml/min using methanol and 0.5% phosphoric acid at ratios of 5: 95, 70:30, 90:10, and 5:95 at 0-17, 17-18, 18-20.5 and 20.5-25 min, respectively.…”
Section: Identification Of Compounds By High-performance Liquid Chrommentioning
confidence: 99%